1982
DOI: 10.1007/bf00690582
|View full text |Cite
|
Sign up to set email alerts
|

Papovavirus-related RNA sequences in human neurogenic tumours

Abstract: Thirty-two human brain tumours were investigated for the presence of papovavirus-related RNA sequences. Radiolabelled viral DNAs isolated from SV40, BKV, HDV, and BPV were hybridized in-situ on to tumour kryostat sections under conditions that detect complementary RNA. SV40-related RNA was detectable in 34% of all tumours tested but was not found in normal human brain tissue. SV40-positive tumours included 1/1 angiofibroma, 1/4 astrocytomas, 2/4 metastatic brain tumours, 1/1 melanoma, 3/7 meningiomas, 2/4 neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…A papovavirus antigen has been identified in human meningiomas [73], and DNA hybridization techniques have found BK viral DNA, SV-40 viral DNA, and adenovirus DNA within meningiomas [75][76][77].…”
Section: Virusesmentioning
confidence: 99%
“…A papovavirus antigen has been identified in human meningiomas [73], and DNA hybridization techniques have found BK viral DNA, SV-40 viral DNA, and adenovirus DNA within meningiomas [75][76][77].…”
Section: Virusesmentioning
confidence: 99%
“…Although the demonstration of polyomavirusrelated nucleic acid sequences has been reported in a number of human neural tumors (124)(125)(126), the actual development of gliomas in the centers of the demyelinating lesions of PML has so far been limited to two well-documented reports (127,128), but it is of significance that in both instances the astrocytomas were multiple. That the JC strain of human polyomavirus is potentially capable of transforming human astrocytes would seem likely, but the hypothesis that some gliomas might be due to a nonpermissive infection of astrocytes by the virus of PML remains unproven.…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 99%
“…The history of SV40 and its role in the development of primary brain cancers began soon after its discovery in 1960 when it was demonstrated to induce central nervous system malignancies following injection into newborn hamsters (Eddy et al, 1962;Girardi et al, 1962). Human studies conducted in the 1970s and 1980s identified SV40-positive brain tumors using DNA hybridization techniques or indirect immunofluorescence for viral proteins (Weiss et al, 1975;Tabuchi et al, 1978;Meinke et al, 1979;Krieg et al, 1981;Ibelgaufts and Jones, 1982;Dorries et al, 1987), whereas studies performed in the 1990s and 2000s generally used PCR-based approaches (Bergsagel et al, 1992;Martini et al, 1996;Suzuki et al, 1997;Huang et al, 1999;Krynska et al, 1999;Zhen et al, 1999;Ohgaki et al, 2000;Weggen et al, 2000;Kouhata et al, 2001;Malkin et al, 2001;Engels et al, 2002;Martini et al, 2002).…”
Section: Primary Brain Cancersmentioning
confidence: 99%
“…In all, 11 studies fulfilled the criteria among 16 articles reporting on SV40 and primary human brain cancers through November 2001 (Figure 1) (Weiss et al, 1975;Meinke et al, 1979;Krieg et al, 1981;Ibelgaufts and Jones, 1982;Dorries et al, 1987;Bergsagel et al, 1992;Martini et al, 1996;Suzuki et al, 1997;Zhen et al, 1999;Weggen et al, 2000;Malkin et al, 2001). The adjusted combined effect size (odds ratio (OR)) of the 11 original studies was 3.9 (95% confidence interval (CI), 6-8).…”
Section: Primary Brain Cancersmentioning
confidence: 99%
See 1 more Smart Citation